Bronchoalveolar lavage fluid cell counts in cryptogenic fibrosing alveolitis and their relation to therapy. Issue 5 (May 1980) - Haslam, P L; Turton, C W; Lukoszek, A; Salsbury, A J; Dewar, A; Collins, J V; Turner-Warwick, M
Abstract : Bronchoalveolar lavage was used to sample inflammatory cells from the lungs of 51 patients with cryptogenic fibrosing alveolitis (CFA) (24 smokers, 12 ex-smokers, and 15 non-smokers). The smokers with CFA have been compared with 15 smoking control subjects in whom there was no radiographic abnormality or clinical evidence of chronic bronchitis. Significantly lower volumes of lavage fluid were recovered from the smokers with CFA (p < 0.001) and the fluid contained lower percentages of macrophages (p < 0.01), reflecting increased percentages of eosinophils (p < 0.001) and neutrophils (p < 0.01). Similar changes were seen in the ex-smokers and non-smokers. There was also an increase in the percentages of lymphocytes when the whole group of CFA patients was compared with the control subjects (p less than or equal to 0.05). No significant differences were found when patients with "lone" CFA were compared with those having associated systemic disease. The only feature distinguishing smokers from non-smokers with CFA was the presence of pigmented cytoplasmic inclusions in the macrophages from the smokers (p < 0.001). However, there were lower numbers of pigmented macrophages in the smoking CFA patients by comparison with the control subjects suggesting either a change in phagocytic capacity or turnover rate in this disease. Profiles of differential cell counts in individual patients showed that increases of eosinophils over 3% or neutrophils over 4% or both with lymphocyte counts of less than 11% related to a poor clinical response to corticosteroids, but lymphocyte percentages greater than 11% related to improvement (p < 0.05).